Assessment of a Novel Enhanced Sampling Method for Molecular Simulations of Peptide-membrane Interactions - Tanner, John Douglas (Curtin University, 2020)
Gomesin is a spider-derived peptide with anti-microbial and anti-cancer properties which, like other such peptides, acts by permeabilising cell membranes. A new computer simulation approach was developed and tested to describe the interaction of Gomesin with model membranes. The findings will assist the future development of simulation methods to better understand in detail the molecular mechanism of action of Gomesin and related peptides.